Anasarca Associated with Restrictive Cardiomyopathy in Cats - Froner Argenta , Fernando; Vielmo, Andréia; Slaviero, Mônica; Castilhos da Silva, Carolina; Viana Rufino, Samara; Vieira Amorim da Costa, Fernanda; Kenji Masuda , Eduardo; Sonne, Luciana (Acta Scientiae Veterinariae, 2022)
Background: Cardiomyopathies are a primary heart disorder and are one of the most causes of heart failure and sudden death in cats. Restrictive cardiomyopathy is a diastolic dysfunction resulting from endomyocardial fibrosis, with filling restriction and ventricular distention. In these cases, a poor outcome is expected. Anasarca in animals is often associated with dystocia secondary to congenital changes. In adults, this is a rare condition, since subcutaneous edema in animals with congestive heart failure is an uncommon finding. Therefore, this report describes clinical and pathological findings in an unusual presentation of anasarca in two adult cats with restrictive cardiomyopathy. Cases: A 12-year-old female mixed breed cat (case 1) and a 6-year-old male mixed-breed cat (case 2) were present on an emergent basis at the veterinary hospital with a history of respiratory distress. Case 1 showed on physical examination intense restrictive mixed dyspnea and lethargy, with muffled heart sounds and respiratory noises in cardiorespiratory auscultation. The cat exhibited abdominal distension resulting from ascites. Generalized subcutaneous edema was evident mainly in the abdominal and submandibular areas and the thoracic and pelvic limbs. In these regions, a positive Godet signal was observed. Thoracic radiography revealed pleural effusion, and the cat underwent fluid drainage on both sides of the thoracic cavity. Drainage material was sent to the laboratory for clinical analysis, which indicated that it was a modified transudate. The clinical signs worsened, and the cat was euthanized. In case 2, physical examination showed severe restrictive mixed dyspnea, lethargy, and low body temperature (< 32°C). Abdominal distension resulting from ascites and generalized edema in the subcutaneous tissue with a positive Godet sign was observed. On cardiorespiratory auscultation, cardiac sounds and breathing noises were muffled. Thoracic radiography revealed pleural effusion. The cat was immediately placed in an incubator for clinical stabilization with oxygen therapy and warm-up. After 2 h of hospitalization, thoracentesis and drainage of cavity fluids were performed, which were classified as modified transudate. The patient remained in critical condition during hospitalization, evolving to death. The two cats were referred for a complete post mortem examination. Grossly, both cats showed distension of the abdomen and marked edema of subcutaneous tissue, mainly in the abdominal, ventral cervical, and thoracic and pelvic members. In the abdominal and thoracic cavities, a moderate amount of serous-free liquid, slightly reddish was observed. The heart of both cats was enlarged, with a globose appearance and a slightly whitish epicardium. The left ventricular endocardium was mild and diffusely thick and whitish, in addition to moderate dilation of the left atrium. Histological analyses of the heart showed in both cats moderate and diffuse proliferation of fibrous connective tissue in the endocardial region. Discussion: Restrictive cardiomyopathy has major importance in feline medicine due to its severity and poor outcome. Pleural effusion, pulmonary edema, and ascites are common findings in cats with congestive heart failure; however, generalized subcutaneous edema is uncommon. To the author’s knowledge, there are no published cases in the literature of anasarca in adult cats with restrictive cardiomyopathy. In human cardiology, this presentation is commonly related to congestive heart failure, and it is reported under several conditions, such as restrictive cardiomyopathy and constrictive pericarditis. The present study suggests that anasarca should be included in the list of associated clinical signs suggestive of severe congestive heart failure, mainly related to restrictive cardiomyopathy. Keywords: cardiomyopathy, endomyocardial fibrosis, feline, generalized edema.